A high-temperature organic–inorganic ferroelectric with outstanding switchable dielectric characteristics. Issue 76 (12th October 2017) - Xu, Cong; Zhang, Wenjun; Gao, Linsong; Gan, Xuecheng; Sun, Xiaofan; Cui, Zepeng; Cai, Hong-Ling; Wu, X. S.
Abstract : A new molecular ferroelectric is discovered in an organic–inorganic hybrid compound, (C6 H5 NH3 )2 CdCl4, which undergoes a reversible order–disorder ferroelectric phase transition at 369 K. Abstract : A new molecular ferroelectric is discovered in an organic–inorganic hybrid compound, (C6 H5 NH3 )2 CdCl4, which undergoes a reversible order–disorder ferroelectric phase transition at 369 K and has a spontaneous polarization of about 0.5 μC cm −2, larger than the Rochelle salt. Large dielectric anomaly, pyroelectricity and P–E hysteresis loop were observed to represent the ferroelectricity of the compound. Especially, the dielectric constant at the transition temperature increases more than 40 times than that at room temperature, which indicates potential applications on switches and sensors for its high-temperature response and excellently reversible characterization.